MINIMALLY INVASIVE PROCEDURES USED IN EARLY DIAGNOSIS OF SEVERELY DYSPLASTIC ORAL LESIONS - CRISTINA POPA; ANA MARIA FILIOREANU; CARMEN GABRIELA STELEA (Romanian Society of Oral Rehabilitation, 2017)
Severe prognosis of oral cancer lies in the absence of manifest clinical symptoms at onset of this pathology. Early signs of malignant oral lesions are not easy to discover. Therefore, chances for cure of these patients are greatly diminished also by the late intervention of the specialist doctor. On the other hand, the preventive oncological examination aims to identify any clinical and histopathological modifications of the oral mucosa raising suspicion, especially of the lesions localized in high risk areas for the appearance of malignant lesions. In this context, the epithelial dysplasia is seen as the most important indicator for malignant transformation of oral mucosa. The study aims is to assess the efficiency of the complementary examination using the device ViziLite Plus. It is an additional method used in standard examination with incandescent light. The method based on the principle of chemiluminescence is a non-invasive procedure able to underline the asymptomatic dysplastic lesions in oral cavity. Even if it is not a screening and a perfect diagnosis technology, this device has an accuracy of 100% in discovering any pathological oral lesion. The method is easy to use and many studies showed that it is the best procedure in discovering suspicious oral lesions (with the improvement of visualization of over 60%). Considering all described advantages, ViziLite Plus remains today the most predictive complementary test in the diagnosis of high risk oral lesions